PROBLEMATIKA AKSELERASI PENANGANAN KEMISKINAN NELAYAN DI MASA PANDEMI COVID-19 DI KOTA MAKASSAR - Latief, Muhammad Iqbal; Yunus, Rabina; Marissangan, Hasbi; Djibe, Sultan; Genda, Arsyad (Jurnal Pembangunan Manusia, 2022)
Sustainable development goals, or SDGs, are still difficult to realize, especially the goal of ending poverty in all its forms. The Covid-19 pandemic, which has been around for more than a year, has actually exacerbated the condition of poverty in the community. In the city of Makassar, the poverty rate increased dramatically from 4.1 percent to 7.2 percent during 2020 (Makassar Ministry of Social Affairs data). Ironically, the poor who live on islands such as the people of Kodingareng, Barrang Lompo, Barrang Caddi, Lumu-Lumu, Laikang and others, are now getting poorer because of the Covid-19 outbreak. Therefore, this paper seeks to describe the problems of accelerating the handling of fishermen's poverty during the COVID- 19 pandemic in the city of Makassar in accelerating the SDGs. The method used is descriptive qualitative, and the data processed are secondary data and primary data. This research begins with identification and problem formulation, data collection, data processing and analysis including data classification and reduction, conclusion drawing and verification. The results of this study conclude that, the poorer fishermen on the islands, due to the decreasing number of fish catches, decreasing fish prices, higher operating costs at sea, swelling third party loan funds, social restrictions during the pandemic and the impact of sea sand mining in Makassar. . In addition, the social structure of island fishing communities is still trapped by structural poverty conditions. As a suggestion, it is necessary to accelerate intervention in implementing the implementation of village SDGs so that poor fishermen in the islands of Makassar city can get out of poverty.